Generation of T Cell Receptor Retrogenic Mice. (15th May 2019) - Kong, Yuelin; Jing, Yi; Bettini, Maria
Abstract: The ability to express and study a single T cell receptor (TCR) in vivo is an important aspect of both basic and translational immunological research. Traditionally, this was achieved by using TCR transgenic mice. In the past decade, a more efficient approach for single TCR expression was developed. This relatively rapid and accessible method utilizes retrovirus‐mediated stem cell–based gene transfer and is commonly referred to as the TCR retrogenic approach. In this approach, hematopoietic bone marrow precursors are transduced with retroviral vector carrying both alpha and beta chains of a T cell receptor. After successful transduction, bone marrow is injected into recipient mice, in which T cell development is driven by expression of the vector‐encoded TCR. This article details the materials and methods required to generate TCR retrogenic mice. It is divided into three sections and provides detailed methods for generation of stable retroviral producer cell lines, isolation and optimal transduction of hematopoietic bone marrow cells, and subsequent analysis of TCR retrogenic T cells. A detailed example of such analysis is provided. The current protocol is a culmination of many years of optimization and is the most efficient approach to date. Bone marrow transduction and transfer into recipient mice can now be achieved in a short period of four days. The protocol can be followed in most laboratories with standard biomedical equipment, and is supported by a troubleshooting guide that covers potential pitfalls and unexpected results. © 2019 by John Wiley & Sons, Inc.